Application of the opportunities of tool system ”CUDA” for graphic processors programming in scientific and technical calculation tasks - Dudnik, V.A.; Kudryavtsev, V.I.; Sereda, T.M.; Us, S.A.; Shestakov, M.V. (Вопросы атомной науки и техники, 2009)
The opportunities of technology CUDA (Compute Unified Device Architecture - the unified hardware-software decision for parallel calculations on GPU)of the company NVIDIA were described. The basic differences of the programming language ”C” for GPU from ”usual” language ”C” were selected. The examples of CUDA usage for acceleration of development of applications and realization of algorithms of scientific and technical calculations were given which are carried out by the means of graphic processors (GPGPU) of accelerators GeForce of the eighth generation. The recommendations on optimization of the programs using GPU were resulted. Описано можливостi технологiї "CUDA"(Compute Unified Device Architecture – унiфiкованого програмно- апаратного рiшення для паралельних обчислень на GPU) компанiї NVIDIA. Видiлено основнi вiдмiнностi мови програмування C для GPU вiд "звичайного"С. Дани приклади використання CUDA для прискорення розробки i реалiзацiї алгоритмiв науково-технiчних розрахункiв, виконуваних засобами графiчних процесорiв (GPGPU) прискорювачiв GeForce восьмого поколiння. Приведено рекомендацiї по оптимiзацiї програм, використовуючих GPU. Описаны возможности технологии "CUDA"(Compute Unified Device Architecture – унифицированного программно-аппаратного решения для параллельных вычислений на GPU) компании NVIDIA. Выделены основные отличия языка программирования C для GPU от "обычного"С. Даны примеры использования CUDA для ускорения разработки приложений и реализации алгоритмов научно- технических расчётов, выполняемых средствами графических процессоров (GPGPU) ускорителей GeForce восьмого поколения. Приведены рекомендации по оптимизации программ, использующих GPU.